The effect of individual task conflict on employee creativity: A moderated mediation model. (March 2019) - Li, Ci-Rong; Li, Chun-Xuan; Lin, Chen-Ju
Highlights: Employee information elaboration plays a mediator linking individual task conflict and individual creativity. There are curvilinear relationships between individual task conflict and both individual creativity and employee information elaboration. The curvilinear relationship between individual task conflict and employee information elaboration was moderated by team reflexivity. Abstract: Adopting conflict as a multilevel phenomenon, we theorized and tested how and when individual level task conflict relates to individual creativity. Integrating the motivated information processing view of conflict with social self-preservation theory, we make the case for employee information elaboration being the mediator between individual task conflict and individual creativity. Multisource data were collected from 374 members and their leaders within 57 engineering teams. The results indicated that individual task conflict was positively related to individual creativity through employee information elaboration. Furthermore, we found a curvilinear relationship that individual task conflict has with both individual creativity and employee information elaboration. Finally, we also found that the curvilinear relationship between individual task conflict and employee information elaboration was moderated by team reflexivity, such that a positive relationship was strengthened and a negative relationship weakened, in higher team reflexivity, but not in lower team reflexivity.